Status kesehatan dan asupan mikronutrien vegetarian dan nonvegetarian di Bali - Ni Ketut Sutiari; Ali Khomsan; Hadi Riyadi; Faisal Anwar; Desak Putu Yuli Kurniati; Widya Astuti (Jurnal Gizi Klinik Indonesia, 2021)
Health status and micronutrient intake among vegetarian and non-vegetarian in BaliBackground: Several studies have reported that vegetarian diets have health benefits for those adopting the diets.Objective: This study aimed to compare anemia status and micronutrient intake between vegetarians and non-vegetarians in Bali.Methods: This cross-sectional study was conducted in Bali. A total of 240 samples consisting of 160 vegetarians and 80 non-vegetarians were randomly selected. Hemoglobin (Hb) and fasting blood sugar levels were measured using the cyanmethemoglobin method and enzymatic colorimetric, respectively. Meanwhile, the data on micronutrient intakes were collected by interviews using the semi-quantitative food frequency questionnaire (SQFFQ). The data were analyzed using descriptive statistics, and the Mann-Whitney test was performed to analyze the differences.Results: The study’s results showed that the mean Hb levels in the vegetarian group were significantly lower than non-vegetarians (p=0.002; p<0.05), and the anemia status in vegetarian women were higher (22.5%) than non-vegetarian women (2.5%). The mean fasting blood glucose level in non-vegetarians was significantly higher than in the vegetarian group (p=0.000; p<0.05). There were no differences in zinc (Zn) intake between vegetarians and non-vegetarians, but there were significant differences (p<0.05) in vitamin C, vitamin D, vitamin B12, folic acid, magnesium (Mg), calcium (Ca), and iron (Fe) intakes.Conclusions: There were differences in anemia status and fasting blood glucose levels between vegetarians and non-vegetarians. The fasting blood glucose levels of non-vegetarians were higher than vegetarians, and there were differences in the intake of certain micronutrients between vegetarians and non-vegetarians.